Exploring Exercise Dependence: A Qualitative Study of Filipino Fitness Enthusiasts’ Motivations for Excessive Workouts - Habig, Edith; Calimpon, Jessica May; Ramos, David Paul (Journal of Interdisciplinary Perspectives, 2025)
Although physical activity is essential for a healthier lifestyle, excessive exercise can lead to exercise dependence and pose significant health risks. Understanding why individuals persist in prolonged exercising, despite potential harm, is essential in addressing this emerging health concern. Hence, this study examined the motivations behind exercise dependence among at-risk Filipino fitness enthusiasts and the factors that contribute to excessive exercise. Using a descriptive qualitative approach, ten fitness enthusiasts aged 18 to 57 years, from Alabang, Muntinlupa City, and Mandaluyong City, were interviewed. The participants were selected due to their high scores on the Exercise Dependence Scale-Revised. Thematic analysis revealed three interconnected themes: 1) motivations to exercise, including health-related goals, weight management, and enhancing appearance; 2) limited awareness about the adverse consequences of excessive exercise; and 3) maladaptive behaviors stemming from misconceptions about exercise outcomes. These themes demonstrate how initial health motivations can lead to exercise dependence when individuals are misinformed or have limited awareness. Consequently, these behaviors contribute to unhealthy exercise habits. This study highlights the need to raise awareness about the risks associated with exercise dependence, aiming to reduce its adverse effects on health and well-being.